2023
DOI: 10.3389/fpsyt.2023.1168302
|View full text |Cite
|
Sign up to set email alerts
|

Anti-leucine-rich glioma-inactivated 1 encephalitis revealed by a manic episode: insights from frontal lobe dysfunction in neuropsychiatry through neuropsychology and metabolic imaging. A case report

Abstract: BackgroundAnti-leucine-rich glioma-inactivated 1 (LGI1) encephalitis is a limbic encephalitis that rarely presents as an isolated psychiatric syndrome.Case presentationA 70-year-old patient first presented with behavioral disorder including hyperactivity, euphoria, with disinhibition and accelerated speech associated with severe insomnia and cognitive disorder. A manic episode was diagnosed and he received various psychotropic medications with no improvement. Invesitgations were negative (MRI showed T2 aspecif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…8 Taken together, the present and the previous cases indicate diversity in the characteristics, age of onset, and the duration of isolated psychiatric symptoms. [6][7][8] In the present case, the main symptoms at the first visit to our hospital were hallucinations and delusions, and acute psychotic disorder was also a differential diagnosis. Anti-NMDA receptor encephalitis tends to develop more frequently in young women and is associated with tumors.…”
Section: Discussionmentioning
confidence: 51%
See 4 more Smart Citations
“…8 Taken together, the present and the previous cases indicate diversity in the characteristics, age of onset, and the duration of isolated psychiatric symptoms. [6][7][8] In the present case, the main symptoms at the first visit to our hospital were hallucinations and delusions, and acute psychotic disorder was also a differential diagnosis. Anti-NMDA receptor encephalitis tends to develop more frequently in young women and is associated with tumors.…”
Section: Discussionmentioning
confidence: 51%
“…Furthermore, in patients with anti-LGI1 encephalitis with FBDSs, ictal changes may not be seen on EEG, 10,11 and FBDSS may even be misdiagnosed as psychogenic seizures. 11 In fact, the previous reports showed that patients developing isolated psychiatric symptoms in the initial phase were diagnosed with psychiatric disorders, [6][7][8] and there was a long interval before anti-LGI1 encephalitis was diagnosed. 6,8 The MRI findings of anti-LGI1 encephalitis are characterized by abnormal findings in the medial temporal lobes, 1 although approximately half the cases of anti-LGI1 encephalitis accompanied by FBDSs do not show abnormal findings in the medial temporal lobes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations